Femonationalism is not populism - Farris, Sara (Scenari, 2021)
In this article the demands for women’s rights are examined from an unlikely collection of right-wing nationalist political parties, neoliberals, and some feminist theorists and policy makers. Focusing on contemporary political problems and right-wing populist movements in Europe (Lega, Front National etc.), the author labels the exploitation of feminist themes by xenophobic campaigns and the instrumental use of “pseudo-feminist” arguments to construct their own narrative as “femonationalism”. A formalistic definition of the concept of populism, such as that proposed by Ernesto Laclau, is not sufficient to explain this strategy. On the contrary, post-colonial theories about nationalism and race allow us to understand the historical background of certain representations of Muslim and non-Western migrants, as much as the role played by gender in the construction of national identity. Current right-wing political movements have to be understood on the basis of nationalism and racist institutions.